Theriogenology teaching manual : compiled in a very simple way - Kassa, Araya (Herstellung : Lap Lambert Academic Publishing, 2011)
The subject theriogenolgy is wide by its nature. The manual tried to cover both sexes with particular emphasis for female animals. The anatomy, the reproductive physiology, problems related with reproductive organs, infertility problems in sexes, gestation and pregnancy diagnosis, problems during gestation periods, postpartum periods and post partum problems, semenology and semen collection techniques and artificial insemination are some of the points addressed by the manual. To have a better understanding and for the purpose of comparison the manual also contains some points from humans/woman. The manual is so detail in its scope and able to provide sufficient information to the readers. I believe that the teaching manual contains all-in-one and it is open to be refined and enriched. I hope readers will like it how I tried to organize it. I need the manual to be published because I do not want this compiled work to be left on the shelf till my graduation in the field that I am attending now.
Includes bibliographical references.
Keywords: Theriogenology